E-Business Software Product Line Methodology Based on SMEs Characteristics - Ni Made Satvika Iswari; Eko Kuswardono Budiardjo; Zainal Arifin Hasibuan (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2022)
The growth of Small and Medium Enterprises (SMEs) will certainly have a positive influence on economic development in a country. However, many SMEs struggle to survive, grow, and show limited productivity. It was recorded that there were around 63.9% of SMEs in Indonesia whose turnover had decreased by more than 30% during the COVID-19 pandemic. Among the factors that cause the low survival rate of SMEs, a factor that is considered critical is the lack of success in the use of e-business. The use of e-business by SMEs is not a one-size-fits-all solution, because SMEs have various characteristics. In this study, an E-Business Software Product Line Methodology based on SMEs characteristics was proposed using Software Product Line Engineering (SPLE) approach. In general, the proposed methodology was sufficient to describe the aspects needed in building a software development methodology. Aspects that had not been described were those related to software project management. The proposed methodology is useful for building an e-business application platform that can be customized based on SMEs characteristics.